Sudden Oak Death - Philip F. Harmon; Carrie L. Harmon (EDIS)
Sudden oak death is a new disease capable of causing a range of symptoms from leaf spots to plant death on many woody hosts. Because sudden oak death is a new disease, much about the pathogen, host range, and the disease epidemiology is unknown. This document is PP197, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March 2004.